The Economic Value of Statistical Quality Control: Cost Reduction and Competitive Advantage in Manufacturing (European Journal of Marketing and Economics, 2025)
In modern manufacturing, quality has transitioned from a technical necessity to a strategic economic asset. This study examines how statistical quality control (SQC) drives measurable financial benefits by reducing defects, minimizing waste, and enhancing process efficiency. Focusing on two fundamental statistical techniques—parameter estimation and hypothesis testing—we demonstrate their pivotal role in identifying process variations and validating improvements. Through practical examples, we illustrate how confidence intervals precisely locate quality deviations, while hypothesis tests confirm the effectiveness of corrective measures, enabling optimal resource allocation. Our analysis quantifies both direct cost savings (e.g., reduced scrap, rework, and warranty claims) and indirect economic gains (e.g., improved customer satisfaction and market positioning). The results show that implementing rigorous SQC protocols delivers rapid return on investment (ROI) and fosters long-term competitive advantage. We argue that integrating statistical methods into production workflows is not merely a quality initiative but a strategic economic decision that enhances sustainable performance. The paper concludes with actionable insights for manufacturers seeking to leverage SQC for financial and operational excellence.
Keywords: statistical quality control, manufacturing economics, cost reduction, process optimization, hypothesis testing, parameter estimation, competitive advantage, ROI